Initial Use of Endothelial Progenitor Cells Capturing Stents in Paediatric Congenital Heart Disease - Cabanelas, N (2014)
INTRODUCTION: Stenosis, mediated by neointimal hyperplasia and thrombosis, is a major limiting factor in successful stent implantation. The introduction of a stent, coated in its endoluminal surface by antihuman CD34 antibodies with endothelial progenitor cell-capturing properties, opens the possibility of promoting a rapid and normal functioning coverage by endothelium and thus avoids both an excessive cell proliferation within stent and the need for long-term dual antiplatelet therapy. These stents, developed for adult coronary artery disease, have not yet been implanted in children or in those with congenital heart disease. OBJECTIVE AND METHODS: In this paper, we describe the implantation of Genous® stents in three children with cyanotic congenital heart disease and obstructed systemic-to-pulmonary shunts. We describe the use of this stent and address its potential feasibility in paediatric congenital heart disease. RESULTS: To maintain the patency of two modified Blalock-Taussig shunts and one ductus arteriosus, four Genous® stents were implanted in three infants with cyanotic heart disease. All procedures were immediately successful, with resolution of stenosis and improvement in transcutaneous oxygen saturation from 66% ± 3.6% to 92% ± 2.6%. In the follow-up, one stent had no occlusion; however, the remaining two had partial occlusion after 5 and 5.5 months, which were successfully managed with balloon dilatation preceding elective definitive surgical correction. CONCLUSION: In our preliminary experience, we demonstrated that Genous® stent implantation was feasible in infants with complex congenital heart disease. Additional studies with larger samples and longer follow-up are required to confirm the potential benefits of this technology in this clinical setting.